FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN MOBILISASI DINI POST OPERASI APENDIKTOMI DI RUANGAN BEDAH BLUD DR.M.M.DUNDA LIMBOTO GORONTALO TAHUN 2013 - Pipin Yunus; Anik Indarwati (-, 2021)
Factors Associated With Early Implementation of Post Operation Mobilization Apendiktomi In Non Surgical Blud Dr.MMDunda Limboto Appendicitis is an inflammation of the appendix disease caused by the appendix lumen of the appendix. One is with Apendiktomy Management. The purpose of this study was to determine the factors associated with the implementation of early mobilization postoperative surgical apendiktomi in room BLUD Dr.MMDunda Limboto. The study design used is descriptive cross sectional correlation. Populations all postoperative patients apendiktomi in room Surgery BLUD Dr.MMDunda Limboto were 21 people and sampling techniques with a total sampling technique to sample 21 people. Analysis carried out in stages (1) Univariate analysis using frequency distribution. (2) Bivariate analysis to examine the relationship between variables. Statistically test results show that there is a relationship between motivation, disease processes, social support, and knowledge with the implementation of early mobilization Postoperative Apendiktomi BLUD dr. M.M Dunda Limboto